MEMBANGUN KESADARAN UMKM TERHADAP POTENSI PENJUALAN MELALUI ONLINE SHOP DI DESA BANYURASA, KECAMATAN SUKAHENING, KABUPATEN TASIKMALAYA - Alrisqi, Narisa Nur; Effendi, Tasya; Julimah, Ratna; Sopiatunnisa, Neneng; Sholihat, Lisna Mardiana (Pusat Penelitian dan Pengabdian Kepada Masyarakat, 2025)
MSME players in Banyurasa Village, Sukahening Subdistrict, face constraints in the lack of utilization of digital platforms for marketing, limiting competitiveness and market expansion. This service program aims to improve the digital literacy and skills of MSME actors through training in online shop management and digital marketing. The research method used is descriptive qualitative, with data collection techniques through interviews, observation, and documentation. The activity stages include initial data collection to understand business conditions, field surveys to identify challenges and potentials, and a seminar themed